Representatives of Bacillus from Deep-Water Bottom Sediments of the Black Sea – Producers of Elastases, Fibrin(ogen)ases, and Collagenases - Gudzenko, O.V.; Varbanets, L.D.; Ivanytsia, V.O.; Shtenikov, M.D.; Гудзенко, О.В.; Варбанець, Л.Д.; Іваниця, В.О.; Штеніков, М.Д. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
Among microorganisms, bacteria and fungi are reported to be good sources of different types of enzymes, in particular proteases, which have a broad range of applications in industrial processes and products and are representative of most worldwide enzyme sales. The genus Bacillus is probably the most important bacterial source of proteases and is capable of producing high yields of neutral and alkaline proteolytic enzymes with remarkable properties, such as high stability toward extreme temperatures, pH, organic solvents, detergents, and oxidizing compounds. Earlier we have shown the ability of a number of strains of Bacillus sp. isolated from the bottom sediments of the Black Sea: 051, 054, 052 (depth 2080 m), and 247 (depth 1888 m) to display elastase activity (20.83 U/mL, 19.96 U/mL, 15.62 U/mL and 12.15 U/mL, respectively). Since the bacterial population of the deep-sea bottom sediments of the Black Sea has been little studied, the purpose of this work was to search for effective protease producers among the microbiota of the Black Sea water and sediments obtained from its various depths. Methods. The objects of the study were 20 cultures isolated from bottom sediments from 4 points at depths of 888–2080 m in the Black Sea. The cultures were grown under conditions of deep cultivation at 28 °С, with a mixing speed of the nutrient medium of 230 rpm for 2 days. Methods for determining proteolytic (elastolytic, fibrinolytic, fibrinogenolytic, and collagenase) activity in the culture liquid supernatant were used. Results. The research on the ability of the supernatants of the studied cultures to hydrolyze various proteolytic substrates has shown that promising for further investigations can be cultures 248 and 249, isolated under the same conditions (1499 m, 15–20 cm), but being representatives of different species, namely Bacillus subtilis and B. licheniformis, respectively. Supernatants of their culture liquids showed the greatest activity toward fibrin (20.5 U/mL and 19.0 U/mL) and fibrinogen (21.66 U/mL and 20 U/mL, respectively), while cultures of B. licheniformis 249 (1499 m, 15–20 cm), Priestia megaterium 55 (1537 m, 0–5 cm), and B. subtilis 1 (1499 m, 5–10 cm), which were isolated under different conditions, showed high activity toward elastin (33.3 U/mL, 31.2 U/mL and 29 U/mL, respectively). B. subtilis 1 is able to hydrolyze all investigated proteolytic substrates: elastin, fibrin, fibrinogen, and collagen, but the level of these activities was lower than in the above-mentioned strains. Conclusions. According to their catalytic properties, a number of representatives of bacteria Bacillus licheniformis 249, Priestia megaterium 55, and Bacillus subtilis 1 isolated from the deep-water bottom sediments of the Black sea may be promising for further research as producers of enzymes with elastolytic, fibrinolytic, and fibrinogenolytic activity.